Kalkulasi Harga Jual Bibit Ikan Nila Pada Usaha Budidaya Keramba Ikan Pak Ahmad Di Desa Sumber Sari Kecamatan Loa Kulu - Juanda, Rendy (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2015)
The current problem at Nila Pak Ahmad fish farming business in Desa Sumber Sari is not yet able to determine the selling price of tilapia fish production with the amount of production cost incurred according to the calculation of accounting rule, because so far only based on the estimation and only compare the price Selling on another place based on the same product. So the business of fish cultivation Tilapia Pak Ahmad find it difficult to know for sure the benefits obtained with the truth. The data used are gross income, labor cost, operational cost and overhead cost for one year 2014. Analyzer used full costing with mark up method. Based on the calculation of the selling price of tilapia obtained from the sum of the cost of production known that the selling price of Nila fish in the cultivation of fish cage Pak Ahmad according to the analysis of Rp. 192, - / one fish while the selling price according to the owner of the cultivation business Pak Ahmad fish cage for this amount of Rp. 200 or there is the price difference amount Rp. 8 or Rp. 8,000 /one thousand fish.With the results of the above analysis, seen selling price applied business owner cultivation Pak Ahmad fish cage higher than the results of the analysis. So it can be concluded this business is still operating normally or still can get the desired profit Rp. 8,000,000. So that the selling price of fish by the owner of the cultivation of Pak Ahmad fish cage should be adjusted again in order to be able to generate optimal profit but still in the stage of the consumer's affordable price limit. So the hypothesis proposed earlier "That the selling price of tilapia on the Business Cultivation Keramba Fish Pak Ahmad In Sumber Sari Village District Loa Kulu lower than the results of analysis according to the rules of accounting" was rejected Keywords: Full costing, Selling Price, Variable costing